Impact Assesment of Municipal Solid Waste on Ground Water Quality in and around Kapulauppada Dumpyard in GVMC using Remote Sensing and GIS Techniques - Dileep, Killana; Jaishankar, G; Rao, Jagadeeswara; Durgadevi, M; Srinivas, M.D.R (International Journal of Computer Sciences and Engineering, 2025)
The improper dumping of the municipal solid waste in the Kapulauppada area of Greater Visakhapatnam Municipal Corporation (GVMC) leads to serious pollution threat to the ground water of the study area. Thus, the present study deals with the physio-chemical parameters of the ground water in the dumping yard of Kapulauppada area which is occupying about 100 acres of the area. The investigation involves the detailed field survey and collection of data and analysis and displaying the results. In the study area, 21 different ground water samples have been collected in and around Kapulauppada. The analysis of the physio-chemical parameters of ground water like pH, total hardness, total alkalinity, chlorides, total dissolved solids, calcium, magnesium, turbidity and electrical conductivity are studied. The results are compared with Bureau of Indian Standards (BIS). Based on the standard calculation methods, the standard parameters such as Water Quality Index (WQI) is calculated for each sample location. The results show that 66.66 % of water is poor for drinking purpose, 23.8% of water is good water and 9.5% of water is excellent for drinking purpose. So improper dumping of municipal solid waste is leading to the pollution of the ground water in the Kapulauppada area.